Analisis Risiko Bahaya pada Pekerja di Tempat Penampungan Sampah Terpadu Reduce Reuse Recycle (TPST 3R) Mulyoagung Bersatu Dau Kabupaten Malang - Alma, Lucky Radita; Ulfah, Nurnaningsih Herya; Utomo, Yudhi; Afifah, Afifah; Adawiyah, Uciatul; Nur Kholifah, Wakhi Datul; Merillarosa, Iing (citeus, 2019)
Integrated waste bin of Reduce Reuse Recycle (TPST 3R) Mulyoagung Bersatu Dau is one of the TPS in Malang Regency. Every day the TPST carry out various kinds of garbage from the community around Dau District before being transported to the final rubbish dump. The waste management activities carried out by the workers, have the potential for accidents and diseases caused by work, especially the implementation of health and safety has not been done according to standards. The purpose of this study was to determine the description of hazard risks to workers in TPST 3R Mulyoagung Bersatu District of Dau Malang Regency. This research was a descriptive observational study. Research respondents were 36 people. The results of this study, as many as 58% of workers stated that the danger that